A Lifestyle with Moderate-to-Vigorous Physical Activity Lowers Resting Heart Rate in Adolescents - Stanley Lovell Hanson; Christiane Marlene Sooai (CV. Publikasi Indonesia, 2026)
Physical activity plays an important role in maintaining cardiovascular health and preventing early cardiometabolic risk. However, global evidence indicates that a large proportion of adolescents do not meet the recommended levels of physical activity, which may negatively influence cardiovascular indicators such as resting heart rate (RHR). Elevated RHR has been widely recognized as an early marker of cardiovascular risk and autonomic imbalance. This study aimed to analyze the association between physical activity levels and resting heart rate among adolescents aged 20–24 years. This research employed an analytic observational design with a cross-sectional approach. A total of 100 participants were recruited using convenience sampling from the Faculty of Medicine, Duta Wacana Christian University, Yogyakarta. Physical activity levels were assessed using the International Physical Activity Questionnaire Long Form (IPAQ-L), while resting heart rate was measured through radial pulse palpation after a five-minute seated rest. Statistical analysis was conducted using SPSS software with Chi-square testing. The results showed that 47% of participants engaged in moderate physical activity, 24% in vigorous activity, and 29% in low activity. Most participants (62%) had a resting heart rate above 80 bpm. A significant inverse association was found between physical activity level and resting heart rate (p = 0.019), indicating that adolescents with higher levels of physical activity tended to have lower resting heart rates. In conclusion, moderate-to-vigorous physical activity is associated with healthier resting heart rate values, suggesting improved cardiovascular function in adolescents.